Longitudinal changes in sputum and blood inflammatory mediators during FeNO suppression testing. Issue 9 (8th July 2022) - Couillard, Simon; Shrimanker, Rahul; Lemaire-Paquette, Samuel; Hynes, Gareth M; Borg, Catherine; Connolly, Clare; Thulborn, Samantha Jane; Moran, Angela; Poole, Sarah; Morgan, Sophie; Powell, Timothy; Pavord, Ian; et al.
Abstract : To explore whether fractional exhaled nitric oxide (FeNO) non-suppression identifies corticosteroid resistance, we analysed inflammatory mediator changes during a FeNO suppression test with monitored high-intensity corticosteroid therapy. In linear mixed-effects models analysed over time, the 15 clinically distinct 'suppressors' (ie, ≥ 42% FeNO suppression) normalised Asthma Control Questionnaire scores (mean±SD, start to end of test: 2.8±1.4 to 1.4±0.9, p<0.0001) and sputum eosinophil counts (median (IQR), start to end of test: 29% (6%–41%) to 1% (1%–5%), p=0.0003) while significantly decreasing sputum prostaglandin D2 (254 (89–894) to 93 (49–209) pg/mL, p=0.004) and numerically decreasing other type-2 cytokine, chemokine and alarmin levels. In comparison, the 19 non-suppressors had persistent sputum eosinophilia (10% (1%–67%) despite high-intensity therapy) with raised end-test inflammatory mediator levels (1.9 (0.9–2.8)-fold greater than suppressors). FeNO non-suppression during monitored treatment implies biological corticosteroid resistance.